Dimensional Analysis Organization Design; Case LEMDIKLAT POLRI Training Certification Institute - Fitri Kurnianingsih; Adi Gunawan Sofwan; Mahadiansar Mahadiansar (Universitas Muhammadiyah Tapanuli Selatan, 2021)
LSP Lemdiklat Polri has a very strategic role in structuring the management of human resources of the apparatus, especially in ensuring and maintaining the competence of Polri's human resources and other police functions. However, the current organizational structure and work procedures of the National Police Institute of Education and Training are still not in accordance with the workload that must be carried out. Organizational structures are generally an integral part of carrying out their functions and tasks in a structured manner in order to play a role in realizing the vision and mission of the organization itself. Focus and research locus on the analysis of the organizational structure design of the Professional Certification Institute for Education and Training of the Indonesian National Police (LSP LEMDIKLAT POLRI), As for the research method used using literature study based on existing secondary data. The results show that the ideal design of the organizational structure consisting of complexity and centralization and formalization in general, the respondents have a concern for the activities of the LSP LEMDIKLAT POLRI in their environment. The researcher also gives the first conclusion that the LSP LEMDIKLAT POLRI requires improvement in terms of departmentalization and specialization to improve the quality of POLRI personnel, secondly to strengthen regulations and rules as a form of control to ensure and maintain competence in certification services for non-INP police function bearers.